Achieving Energy Savings by Intelligent Transportation Systems Investments in the Context of Smart Cities - Chen, Yang; Ardila-Gomez, Arturo; Frame, Gladys (Elsevier, 2017)
Investments in intelligent transportation systems (ITS) are beginning to take place in the context of smart city initiatives in many cities. Energy efficiency and emissions reduction are becoming essential rationales for such investments. It is important, therefore, to understand under what conditions investments in ITS in the context of smart cities produce energy savings. We reviewed existing literature, conducted case studies and interviews, and found that the smart cities context has transformed traditional ITS into “smart mobility” with three major characteristics: people-centric, data-driven, and powered by bottom-up innovations.